Incorporation of calcium salts into xanthan gum matrices: hydration, erosion and drug release characteristics. (3rd October 2015) - Groves, Emma; Chaw, Cheng Shu
Abstract: Xanthan gum (XG), a hydrophilic biopolymer with modified release properties, was used to produce directly compressed matrix tablets containing a model drug, sodium p -aminosalicylate. Three formulations were prepared, each containing a different calcium dihydrate salt: calcium chloride, calcium sulfate or dibasic calcium phosphate. The aim of the investigation was to relate the calcium ion content and solubility of the calcium salt to the in vitro drug release profile of the xanthan matrices. Tablet hydration, erosion and drug release were determined in distilled water using the British Pharmacopoeia (BP) paddle method. The data showed that the overall drug release was the greatest with addition of calcium sulfate, followed by calcium chloride and dibasic calcium phosphate. The chloride salt formulation displayed the greatest percentage erosion due to rapid mass loss during the initial phase, followed by those with sulfate or phosphate salts. As xanthan gel viscosity increased and drug release was also found to be lower, it can be concluded that drug release is influenced by the solubility of the salt present in the formulation, since these parameters determine the viscosity and structure of the gel layer.